(untitled) (Scientific journal of the Fergana State University, 2025)
The article talks about landscapes and its diversity, as well as prospects for its use. Also, the role, fundamental and practical importance of the landscape in the system of geographical knowledge is analyzed, and the main methods of determining the specific aspects of the approaches to the use of landscapes are emphasized. The various approaches are covered, but they all serve the human factor. In addition, proposals for environmental protection are presented.